2016
DOI: 10.1111/eci.12416
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in circulating plasmacytoid dendritic cells during short‐term systemic normobaric hypoxia

Abstract: We show a significant decrease in circulating pDCs during hypoxia in parallel to a pro-inflammatory response. Further studies are necessary to evaluate whether the decrease in circulating pDCs might be the result of an enhanced tissue recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…At an altitude of 3,000 m, the number of circulating dendritic cells in human plasma is significantly reduced ( 36 ). At an altitude of 5,000 m, plasmacytoid dendritic cells in human plasma are reduced, and the TNF-α and IL-6 contents are significantly increased ( 37 ). We found that several genes, including NKIRAS2, IKBKE, and TRIM7, were involved in immunoregulation and were lncRNA target genes ( 38 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…At an altitude of 3,000 m, the number of circulating dendritic cells in human plasma is significantly reduced ( 36 ). At an altitude of 5,000 m, plasmacytoid dendritic cells in human plasma are reduced, and the TNF-α and IL-6 contents are significantly increased ( 37 ). We found that several genes, including NKIRAS2, IKBKE, and TRIM7, were involved in immunoregulation and were lncRNA target genes ( 38 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some reports, hypoxia increases the ability of DCs to interact with cytotoxic T cells [159]. Hypoxia has been shown to decrease circulating plasmacytoid DCs with corresponding increase in TNF‐α and IL‐6, although increase in CXCL12 could signify tissue migration [160]. One experiment demonstrated that DCs without HIF‐1α had less CD278 on their cell surface, and the T cells in co‐culture produced less granzyme B mRNA [161].…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…By profiling a large number of immune molecules using Luminex array, we identified multiple molecular changes associated with systemic hypoxia, some of which have been previously reported in humans and animals exposed to hypoxia. For example, elevated blood levels of IL-6, TNF-α and IL-1β have been reported in high-altitude-associated hypoxia [35] and in experimental hypoxia [51][52][53][54][55][56][57][58] using enzymelinked immunosorbent assay (ELISA) to measure a small number of cytokines. In the retina, we found that 4 molecules were upregulated in systemic hypoxia: VEGF, IL-1β, IL-22, and MCP3.…”
Section: Discussionmentioning
confidence: 99%